Peningkatkan Kompetensi Manajerial Pendidikan Kepala Madrasah Melalui Pembinaan Oleh Pengawas Madrasah - Musbahaeri Musbahaeri (EKSPOSE, 2017)
Madrasah supervisors who have the task of developing managerial education are expected to be able to play an active role in improving the managerial competence of the madrasa head. Madrasah supervisors are required to be active, creative, and innovative in applying and developing managerial supervision of education methods, namely monitoring and evaluation methods, reflection and Focus Group Discussion (FGD), Delphi, and workshops. Through this guidance, the headmaster will share, add insight, and consult with the madrasa supervisor so that in the end there will be an increase in managerial competence in education. The results of coaching by supervisors will be followed up by the madrasa head in managing the madrasa, and followed up by the madrasah supervisor in planning the next coaching, and followed up by the government in preparing the Shopping Professional Development program (PKB) for madrasah supervisors.